Integrating psychological strengths under the umbrella of personality science: Rethinking the definition, measurement, and modification of strengths. Issue 1 (2nd January 2019) - Goodman, Fallon R.; Disabato, David J.; Kashdan, Todd B.
ABSTRACT: Following the advent of modern positive psychology, there has been a surge of empirical research on strengths and a call for incorporating strengths into clinical models of psychopathology. In this review, we conceptualize strengths as a subset of personality traits and dissect the criteria used to define strengths. In hopes of improving theoretical models of strengths, we reconsider the personal choice to deploy strengths, the implications of strength use for well-being, and the costs of over-relying on particular strengths. As an illustration, we critically examine a new model of strengths with suggestions for defining, measuring, and developing interventions for strengths. These insights are offered to encourage critical examination of the conditions under which strengths best facilitate well-being.